Florida 2003 Short, Mid, and Full Season Corn Variety Tests for Silage and Grain - David L. Wright; James J. Marois; P. J. Wiatrak; B. Kidd (EDIS)
The objective of the corn variety trials was to compare various corn varieties for silage and grain yields grown under North Florida weather conditions. The studies were conduced on a Dothan sandy loam (fine loamy siliceous, thermic Plinthic Kandiudult) at the North Florida Research and Education Center (NFREC) / University of Florida, Quincy, Florida in 2003. This document is SS-AGR-160, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2004.